Psychosocial therapy model to reduce anxiety levels in hemodialysis patients - Ariyanto, Fajar; Pratiwi, Arum; Hudiyawati, Dian (MEDISAINS, 2024)
Background: Chronic kidney disease (CKD) is a global health issue that significantly impacts the quality of life of patients undergoing hemodialysis. Anxiety is one of the common psychological challenges faced by these patients. While various studies have addressed psychological and social interventions, most have focused on only one aspect, such as family support or psychological therapy, without considering the biological, social, and spiritual needs simultaneously. No research has integrated all these dimensions into a holistic approach.Purpose: This study aims to develop and evaluate a holistic nursing management model that combines all of these aspects to reduce anxiety levels for hemodialysis patients.Methods: This study used a mixed-method approach with an action research design. It was conducted at the Klaten Islamic Hospital. The population in the study was patients undergoing hemodialysis; as many as 15 patients participated in this study. The holistic nursing module was tested in five sessions, each lasting 15-30 minutes. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before and after the intervention.Results: The study's results showed that the average level of anxiety in patients before the intervention was 35.13±3.22; after the intervention, it decreased to 24.87±1.68 (p<0.001).Conclusion: The application of the holistic nursing management model effectively reduced anxiety levels in hemodialysis patients.